Designing immersive narratives of Jugra heritage site for cultural edutainment using mixed reality - Md Zain, Mazarina; Baniyamin, Nurhaya; Ibrahim, Illyani; Rashid, Mizanur; Zakariya, Khalilah; Mohd Mustafah, Yasir (Faculty of Computing and Meta-Technology, Universiti Pendidikan Sultan Idris (UPSI), 2024)
Technology integration in the tourism industry has introduced new possibilities for enhancing visitor experiences and promoting cultural edutainment in heritage tourism. Mixed Reality (MxR) is a promising technology for achieving these goals. By leveraging MxR, cultural heritage sites can provide tourists with engaging and educational experiences, allowing them to delve into the rich history and cultural significance of these sites. However, the quality of content in MxR applications can significantly impact the overall experience and educational value. This research proposes best practices for MxR development in smart heritage tourism, ensuring the delivery of high-quality, culturally authentic, and educational experiences to visitors. A qualitative approach has been adopted to achieve this aim, utilizing the Speak Aloud method to collect data from participants who interacted with the MxR prototype. The study focuses on a case study of the Jugra heritage urban landscape, using it as a basis for developing an MxR prototype. The research encompasses two stages: the first is the design for prototype development, and the second is to test the application for user feedback. Through discussions on prototype design development and user experience testing, the research proposes a storyboard framework as a guideline for designing the MxR environment. This framework serves as a comprehensive blueprint, ensuring that each phase, from data analysis to the final Mixed Reality application, is meticulously designed and executed. Respondents tested the prototype to gather feedback on the prototype's outcomes, enabling refinement of the blueprint for subsequent levels of testing with heritage visitors. The results of this study contribute to the field of MxR development in smart heritage tourism. The research enables developers to create high-quality, culturally authentic, educational MxR experiences by offering guidelines and best practices. Therefore, the application of MxR in cultural heritage enhances the level of visitor engagement and facilitates a more profound comprehension of cultural heritage.